2006
DOI: 10.1007/bf02984658
|View full text |Cite
|
Sign up to set email alerts
|

Predicting human performance by channelized Hotelling observer in discriminating between Alzheimer’s dementia and controls using statistically processed brain perfusion SPECT

Abstract: The performance of the CH observer was similar to that of the human observers, and both were dependent on the image type. This indicates that the CH observer may predict human performance in discriminating Alzheimer's dementia and can be useful for comparing and optimizing image processing methods of brain perfusion SPECT without human observers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…In the literature, they used a channelized Hotelling observer (CHO) method or a principal component analysis (PCA) after setting volume of interests (VOIs) for diagnosing AD or MCI. The merit of using CHO [37] is to differentiate patterns of frequency after Fourier transformation of levels of pixels measured by SPECT between groups. Using voxel data [37], [38] sounds more objective, but a high chance of noise generation may degrade the image quality.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, they used a channelized Hotelling observer (CHO) method or a principal component analysis (PCA) after setting volume of interests (VOIs) for diagnosing AD or MCI. The merit of using CHO [37] is to differentiate patterns of frequency after Fourier transformation of levels of pixels measured by SPECT between groups. Using voxel data [37], [38] sounds more objective, but a high chance of noise generation may degrade the image quality.…”
Section: Discussionmentioning
confidence: 99%
“…His EEG was normal, but brain MRI showed enlargement of the bilateral sylvian fissures. N-isopropyl-p[ 123 I] iodoamphetamine (IMP) SPECT with three-dimensional stereotactic surface projections (3D-SSP) analysis [11] showed relative hypoperfusion in the bilateral temporo-parietal areas, extending from the inferior parietal lobule to the temporo-parietal junction to the middle and inferior temporal gyri.…”
Section: Case Presentationsmentioning
confidence: 99%
“…Based on the results of [7], we chose to explore 4 different numbers of the LG channels, N LG ={5,10,15,30} (the first N LG polynomials) and 4 different values of channel parameter a={15,25,30,45}.…”
Section: Observer Performance Experimentsmentioning
confidence: 99%
“…In the field of MRI, Tisdall and Atkins [6] used the CHO to compare reconstructions of MRI synthetic images. Later on, Shidahara et al [7] used real clinical SPECT images and reported good agreement between performance of a CHO and human in the task of detecting Alzheimer's dementia. In addition, numerical observer studies have been performed for the data sets acquired by inserting simulated lesions in clinically acquired image data of healthy subjects [8], [9], [10].…”
Section: Introductionmentioning
confidence: 96%